Significance of indexes of cytokine status in evaluation of clinical course of hemorrhagic transformation of ischemic stroke - Tatiana А. Nikiforova; Boris M. Doronin; Sergey A. Peskov; Anastasia А. Maruschak (Бюллетень сибирской медицины, 2017)
Aim. To determine the features of cytokine status in ischemic stroke patients with hemorrhagic transformation and its importance in the evaluation of the clinical course and outcome of the disease.Materials and methods. Three groups of patients were examined: 1st group – 66 patients with ischemic stroke without hemorrhagic transformation (IS w/o HT), mean age 63,9 ± 1,3 years; 2nd group – 27 patients with ischemic stroke with hemorrhagic transformation (IS with HT), mean age 65,9 ± 2,5 years; 3rd group – 65 patients with hemorrhagic stroke (HS), mean age 58,8 ± 1,6 years. Determination of cytokine concentration (IL-1β, TNF-α, IL-6, IL-8, IFN-γ, IL-1Ra, IL-10, IL-4) in blood serum was performed on the 1st, 2nd and 10th day of the stroke onset. The control group consisted of 55 – age and sex matched healthy donors.Results. In the group with IS with HT the level of IL-1β on the 1st and 2nd day did not differ from the control values (p > 0,05). In patients with IS with HT the lowest levels of IL-1β and TNF-α were determined on the 1st, 2nd and 10th day of the stoke onset. On the contrary, the highest levels of IL-1Pa were determined on 1st, 2nd day and IL-4 on the 1st, and 10th day (p < 0,05). Blood plasma levels of IL-1β, TNF-α, IL-1Pa, IL-10 in the group of IS with HT depend on the level of neurological disability, pathogenic subtype of stroke and the volume of lesion. Correlations between the level of TNF-α and volume of lesion (r = –0,66, p < 0,05), level of IL-1β and NIHSS score (r = 0,39, p < 0,05), level of IL-1β and Barthel index (r = 0,5, p < 0,05) in acute period of IS with HT were established.Conclusion. Levels of IL-1β and TNF-α are most significant in evaluation of the clinical course and functional outcome of IS with HT.